Real‐world Israeli single institution experience with PET‐PSMA for staging of patients with clinically staged localized prostate carcinoma. Issue 5 (2nd May 2021) - Zarbiv, Yonaton; Peerless, Yehudit; Wygoda, Marc; Orevi, Marina; Meir, Karen; Gofrit, Ofer N.; Yutkin, Vladimir; Frank, Stephen
Abstract: Background: A recent prospective trial, the proPSMA study, showed superior specificity and sensitivity of Positron emission tomography (PET) ‐ Prostate‐specific membrane antigen (PSMA) imaging compared standard Computerized tomography (CT) and bone scan for staging of recently diagnosed high‐risk local prostate carcinoma for curative intent treatment. Aim: To share our experience with false‐positive PET PSMA scans in newly diagnosed intermediate‐risk prostate cancer. Methods and results: Here, we report a series of eight patients who underwent systemic staging using PET‐PSMA with false‐positive results who were ultimately treated with definitive radiation or surgery. Of the eight patients, two patients were diagnosed with favorable intermediate disease, four with unfavorable intermediate risk, and two with high‐risk disease. Seven of eight were shown to have false‐positive bone uptake, one patient had uptake in lung nodules. Three patients underwent bone biopsy and proven benign. The rest of the patients were proven as non‐metastatic radiologically by repeat PSMA, CT, or Magnetic resonance imaging (MRI). All subsequently preceded to definitive localized treatment and remain disease free as of this study. Conclusion: This study emphasizes the importance of prudent clinical judgment when utilizing this highly sensitive imaging technique.